Family cohesion and related factors in school adolescents - Gómez-Velásquez, Santiago; Matagira-Rondón, Giselly; Agudelo-Cifuentes, Maite Catalina; Berbesi-Fernández, Dedsy Yajaira; Morales-Mesa, Santiago Alberto (Universidad y Salud, 2021)
Introduction: The level of cohesion within a family nucleus is useful to characterize connections and relationships established between its members. It also constitutes a fundamental factor in the development of family intervention programs and policies. Objective: To identify factors associated with family cohesion in adolescents from the municipality of Envigado (Colombia). Materials and methods: A cross-sectional study using a primary source of information and a sample of 1008 students from two schools from Envigado. The following instruments were used: family cohesion scale; Zung’s Depression scale; Gismero’s Social Skills scale; and sociodemographic and substance use questions. Results: 61.5% of adolescents were not at risk for alcoholism, 73.8% were not drug dependent, 16.5% were at risk of depression, and 81.7% had adequate social skills. The prevalence of family cohesion was 96.6%. A feeling of satisfaction with their families and absence of depression were associated with good family cohesion. Conclusions: Depression in adolescents and a high level of dissatisfaction towards their family are factors associated with the lack of family cohesion. Factors such as domestic violence, social skills, and use of psychoactive substances did not show an association with the variable of interest.